A just standard: the ethical management of incidental findings in brain imaging research - Graham, M; Hallowell, N; Savulescu, J (Cambridge University Press, 2021)
Neuroimaging research regularly yields “incidental findings”: observations of potential clinical significance in healthy volunteers or patients, but which are unrelated to the purpose or variables of the study.